2013
DOI: 10.1371/journal.pone.0068512
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Climate Change and Globalization on Mosquito Vectors: Evidence from Jeju Island, South Korea on the Potential for Asian Tiger Mosquito (Aedes albopictus) Influxes and Survival from Vietnam Rather Than Japan

Abstract: BackgroundClimate change affects the survival and transmission of arthropod vectors as well as the development rates of vector-borne pathogens. Increased international travel is also an important factor in the spread of vector-borne diseases (VBDs) such as dengue, West Nile, yellow fever, chikungunya, and malaria. Dengue is the most important vector-borne viral disease. An estimated 2.5 billion people are at risk of infection in the world and there are approximately 50 million dengue infections and an estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 18 publications
1
40
0
1
Order By: Relevance
“…The development of mosquito larvae is furthermore promoted with increased surrounding temperature, allowing for faster maturation. Moreover, adult female mosquitos feed more often on blood and thus may transmit infectious agents with higher frequency [25]. Viral replication within the mosquitos is furthermore increased, leading to a reduced extrinsic incubation time with a rise in environmental temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The development of mosquito larvae is furthermore promoted with increased surrounding temperature, allowing for faster maturation. Moreover, adult female mosquitos feed more often on blood and thus may transmit infectious agents with higher frequency [25]. Viral replication within the mosquitos is furthermore increased, leading to a reduced extrinsic incubation time with a rise in environmental temperature.…”
Section: Resultsmentioning
confidence: 99%
“…These elevated temperatures shorten the extrinsic incubation period, so mosquitoes that have acquired infection become infectious sooner; for example, outbreaks of WNV infection appear to occur more frequently in Canada when seasonal temperatures are above average, as these conditions promote rapid build-up of virus in vector mosquitoes and favour extended host-seeking by potentially infected female mosquitoes (26). It has been reported that in Korea and Japan, the duration of the transmission season can be extended by several months when average summer temperatures increase by as little as 5°C (27). Changes in rainfall affect the availability of standing water, which is where mosquitoes lay their eggs and where immature mosquitoes live.…”
Section: Climate Change Will Increase the Risk Of Endemic Mosquito-bomentioning
confidence: 99%
“…Ces températures élevées réduisent la période d'incubation extrinsèque, de sorte que les moustiques qui ont contracté l'infection deviennent infectieux plus tôt; par exemple, les éclosions d'infection par le virus du Nil occidental semblent se produire plus fréquemment au Canada lorsque les températures saisonnières sont supérieures à la moyenne, car ces conditions favorisent l'acquisition rapide du virus chez les moustiques vecteurs et prolongent la recherche d'hôtes par les moustiques femelles potentiellement infectés (26). Il a été signalé qu'en Corée et au Japon, la durée de la saison de transmission peut être prolongée de plusieurs mois lorsque les températures moyennes estivales augmentent d'aussi peu que de 5°C (27). Des changements dans les précipitations augmentent la disponibilité d'eau stagnante, où les moustiques pondent leurs oeufs et où vivent les moustiques qui n'ont pas atteint la maturité.…”
Section: Le Changement Climatique Accroîtra Les Risques De Maladies Eunclassified